Lessons from U.S. Allies in Security Cooperation with Third Countries The Cases of Australia, France, and the United Kingdom - Moroney, Jennifer D. P. (RAND Corporation, 2011)
Several key U.S. allies engage in security cooperation, albeit on a smaller scale than the United States. To see what the U.S. Air Force can learn from these efforts, the authors examined how and why three allies--Australia, France, and the United Kingdom--provide security cooperation and highlight three key areas that could benefit from further collaboration: staff talks, exercises, and training followed by exercises.